(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the analysis of the functioning of neologisms contained in large numbers in modern Internet discourse. The relevance of the study was substantiated, which consists in the objective need for a thorough study and description of neologisms in the English-language Internet discourse (on the example of Internet journals), which most quickly responds to new linguistic phenomena and forms a rich language picture. The concept of neologism was revealed according to the stylistic, psycholinguistic, lexicographic, denotative, concrete historical theories of neologisms. The results of the study can be useful both for linguists, practicing translators, and students studying a foreign language. Also, the results of the study of neologisms on the example of English-language online magazines will help not only enrich such a section of lexicology as neology, but also allow you to clearly see the modern priorities and trends of society, since the new vocabulary is a reflection of culture and values.